A Raman spectroscopic study of diamond and disordered sp3‐carbon in the coesite‐bearing Straumen Eclogite Pod, Norway. (11th October 2012) - SMITH, D. C.; GODARD, G.
Abstract Raman spectral point analysis and Raman mapping have been applied to study the nature of carbon‐bearing microinclusions C3‐1 and C5‐1 within zircon in phengite–kyanite–coesite eclogite sample 62a from the Straumen Eclogite Pod in the Western Gneiss Region (WGR), S.W. Norway. Graphitic carbon is always present with a degree of structural disorder comparable to that found in other ultra high pressure metamorphic (UHPM) terranes; it is compatible with an origin by a partial retrogression of the coexisting diamond due to depressurization by exhumation. Hematite coexists with diamond in C3‐1. In both microinclusions, the Raman wavenumber position of the diamond peak varies from point to point, from the ideal value of 1332 cm−1, frequently down to ∼1328 cm−1 and sometimes down to ∼1322 cm−1 in C3‐1. The bandwidth also increases proportionally. Some spectra reveal doublets with peaks at ∼1328 and ∼1322 cm−1 and even a triplet. These Raman data are discussed in terms of one or other kind of structural disorder of sp3‐carbon, for example metamictization, overtemperature or overpressure, nitrogen impurities and especially stacking disorder, that is, with the possible existence or coexistence of 3C, 2nH and/or 3mR polytypes in a mixture in the same monocrystal. The question of a metamorphic or a contamination origin of the diamond and the disordered sp3‐carbon in slide 62a is evaluated; numerous arguments favour the UHPM origin. These new data contribute to the ongoing debate on the various petrological and geodynamical models (including possible deviatoric stress) for the creation of diamond in UHPM rocks in general. This new locality of diamond at Straumen, the fourth in the WGR but the first in the southwestern part of the UHPM area of the WGR, provides a minimum pressure estimate for UHP metamorphism of ∼3.5 GPa. Taken together with other published P–T estimates, 3.75 ± 0.75 GPa covers all of the estimates of the minimum pressure for coesite‐, diamond‐ or orthopyroxene‐bearing eclogite types in the WGR.